2015
DOI: 10.14310/horm.2002.1632
|View full text |Cite
|
Sign up to set email alerts
|

A short evolutionary history of FSH-stimulated spermatogenesis

Abstract: It is well established in various experimental models that luteinizing hormone (LH) stimulated testosterone (T) production of Leydig cells is the key endocrine stimulus of spermatogenesis.The role of the other gonadotrophin, follicle-stimulating hormone (FSH), is as yet somewhat unclear given that several clinical conditions and experimental models, including men with inactivating FSH receptor (R) mutation and male Fshb and Fshr knockout mice, maintain fairly normal spermatogenesis and fertility. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 84 publications
1
49
0
5
Order By: Relevance
“…The alignment of mLhr and rLhr revealed that the two molecules are overall structurally similar (94.2% identity), reflecting their evolutionary closeness [2, 10], while lower sequence identity was observed by mouse/rat versus human receptor comparison (mLhr versus LHCGR = 81.93%; rLhr versus LHCGR = 83.93%), especially at the hinge region (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alignment of mLhr and rLhr revealed that the two molecules are overall structurally similar (94.2% identity), reflecting their evolutionary closeness [2, 10], while lower sequence identity was observed by mouse/rat versus human receptor comparison (mLhr versus LHCGR = 81.93%; rLhr versus LHCGR = 83.93%), especially at the hinge region (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…LH is produced by the pituitary in a pulsatile fashion, inducing ovulation and maintenance of the corpus luteum in females. In adult males, LH regulates spermatogenesis acting on Leydig cells located in the testes, by controlling testosterone production [2, 3]. hCG is the primate-specific pregnancy hormone produced by trophoblast cells [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, hormonal dominance of spermatogenesis shifted during evolution from FSH to LH [9], whereas FSH has been considered essential for induction of and qualitative and quantitative maintenance for spermatogenesis [49]. The characteristics of FSHβ KO mice were reported by Kumer et al The serum testosterone level was normal and as a result, normal male external genitalia developed.…”
Section: Fsh Stimulation Of Sertoli Cellsmentioning
confidence: 85%
“…However, findings form LuRKO mice revealed the importance of LH action for spermatogenesis. Accordingly, the main regulatory gonadotropin for spermatogenesis has been shifted from FSH dominance to LH dominance [9].…”
mentioning
confidence: 99%